Oxygen reduction activity of carbon-supported Pt-M (M = V, Ni, Cr, Co, and Fe) alloys prepared by nanocapsule method - Yano, Hiroshi (Langmuir : the ACS journal of surfaces and colloids, 2007)
Monodispersed Pt and Pt-M (M = V, Cr, Fe, Co, and Ni) alloy nanoparticles supported on carbon black (denoted as Pt/CB and Pt-M/CB) were prepared by the simultaneous reduction of platinum acetylacetonate and the second metal acetylacetonate within nanocapsules formed in diphenyl ether in the presence of carbon black. For the Pt/CBs, the average Pt diameters measured by scanning transmission electron microscopy (STEM) or X-ray diffraction (XRD) ranged from 2.0 to 2.5 nm, regardless of the catalyst-loading level from 10 to 55 wt % on CB. The alloy composition was found to be well-controlled to the projected value among the supported particles. The activities for the oxygen reduction reaction (ORR) at Nafion-coated catalysts in O2-saturated 0.1 M HClO4 solution were evaluated by using a channel flow electrode (CFE) cell at 30 degrees C. The area-specific ORR activities at Pt-M/CB were found to be 1.3 to 1.8 times higher than that at Pt/CB. The ORR activity increased in the order Pt/CB < Pt-Ni/CB < Pt-Fe/CB < Pt-Co/CB < Pt-V/CB < Pt-Cr/CB